Uterine rupture after high-intensity focused ultrasound ablation of adenomyosis: a case report and literature review - Yinxia Liu; Na Fu; Bin Lv; Yuedong He; Xiaoli Wang (International Journal of Hyperthermia, 2023)
AbstractAim High-intensity focused ultrasound (HIFU) is a non-invasive treatment of adenomyosis. Uterine rupture during pregnancy is a rare adverse event after HIFU treatment, because HIFU treatment results in tissue coagulative necrosis.Methods We reported a case of uterine rupture in a 34-year-old woman. The woman had HIFU treatment for adenomyosis eight months before unplanned pregnancy. She was closely monitored during the pregnancy and the antenatal course was uneventful. At the gestational age of 38 weeks and 2 days, an emergency lower segment cesarean section was performed because of inexplainable abdominal pain. After delivery of the fetus, a 2 × 2 cm serous membrane rupture was observed in the HIFU treatment area.Conclusion Uterine rupture during pregnancy after HIFU is a rare adverse event, however, attention is required during the whole pregnancy in case of unexpected uterine rupture.